2020
DOI: 10.5194/esurf-2020-72
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of topography and soil properties on radiocesium concentrations in forest soils in Fukushima, Japan

Abstract: Abstract. This research collected forest soil samples from Fukushima, Japan, where the 2011 Fukushima Daiichi Nuclear Power Plant (FDNPP) accident contaminated the land. The purpose of this study was to examine how the local topography influenced the radiocesium (Cs-137) accumulation patterns in soils over the years since the accident. As an analytical method, the general additive model (GAM) was used to determine at what percentages the topographic parameters explain Cs-137 contamination levels down to a dept… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Most of the released 134,137 Cs is dispersed but a substantial proportion persists in a resuspension-deposition cycle within the land mass. Consequently, the monitoring of 134,137 Cs in organisms may need to continue until they decay naturally or dissipate in the environment to undetectable levels [4][5][6][7][8][9][10][11]. The processes of the resuspension of 134,137 Cs are not fully understood but many studies have concluded that the concentrations and exposure levels of radioactive Cs were well below regulatory levels, and that their contribution to the long-term exposure of the public from consuming foodstuffs has not been significant in recent years [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the released 134,137 Cs is dispersed but a substantial proportion persists in a resuspension-deposition cycle within the land mass. Consequently, the monitoring of 134,137 Cs in organisms may need to continue until they decay naturally or dissipate in the environment to undetectable levels [4][5][6][7][8][9][10][11]. The processes of the resuspension of 134,137 Cs are not fully understood but many studies have concluded that the concentrations and exposure levels of radioactive Cs were well below regulatory levels, and that their contribution to the long-term exposure of the public from consuming foodstuffs has not been significant in recent years [12][13][14].…”
Section: Introductionmentioning
confidence: 99%